Growth Management and Affordable Housing : Do They Conflict? - Downs, Anthony (Book collections on Project MUSE., 2004)
"Advocates of growth management and smart growth often propose policies that raise housing prices, thereby making housing less affordable to many households trying to buy or rent homes. Such policies include urban growth boundaries, zoning restrictions on multifamily housing, utility district lines, building permit caps, and even construction moratoria. Does this mean there is an inherent conflict between growth management and smart growth on the one hand, and creating more affordable housing on the other? Or can growth management and smart growth promote policies that help increase the supply of affordable housing?" "These issues are critical to the future of affordable housing because so many local communities are adopting various forms of growth management or smart growth in response to growth-related problems. Those problems include rising traffic congestion, the absorption of open space by new subdivisions, and higher taxes to pay for new infrastructures." "This book explores in depth the relationship between growth management and smart growth and affordable housing, drawing material from a symposium on these subjects, sponsored by the Brookings Institution, the U.S. Department of Housing and Urban Development, the National Association of Realtors, and the Fannie Mae Foundation. Contributors seek to inform the debate and provide some useful answers to help the nation accommodate the curtailment of growth in urban and suburban domains while still ensuring a supply of affordable housing."--Jacket